PENGARUH PENGGUNAAN MODUL PEMBELAJARAN TERHADAP HASIL BELAJAR MATA DIKLAT MERANCANG WEB DATABASE UNTUK CONTENT SERVER SISWA KELAS XII TKJ DI SMKN 8 PADANG - Hasmisel Tri Yeni; Kasman Rukun; Almasri Almasri (Universitas Negeri Padang, 2016)
The problem in this research is the fact that is found in the field, namely in SMK Negeri 8 Padang, there are still many students who obtain a class XII TKJ learning outcomes under the criteria of minimum standards on training eye Designing web content server database for the specified school is 78. That is 64.36 % of students who are under KKM dan35,64% of students who are above the KKM. Many factors, among which are the internal factors and external factors, as well as learning media. This study aimed to see whether there is any difference between the results of learning with Learning Module Using the learning outcomes that do not use the Learning Module that direct learning. This research uses experimental approach, this study population were students of class XII TKJ SMK Negeri 8 Padang in academic year 2013/2014. The sampling technique is done randomly. Experimental class is a class that is treated by using the Learning Using Modules and which became the control group is the class that does not use the module but with direct teaching methods. Data collected from the tests of learning outcomes in the form of an objective matter as much as 25 items. Data were analyzed manually to test for normality, homogeneity, and hypothesis testing. From the test results can research on the value of the average student using Module is 78.55 while students who use direct instruction method lower at 75.4 Results of hypothesis by using the formula manually find that thitung7,875> table (1672), so the alternative hypothesis (Ha) is accepted or rejected the null hypothesis (Ho). This means that significantly average results of experimental class learning is greater than the average results of classroom learning control. Keywords: Module, Model Learning, Learning Direct, Control and Experiment